Livelihood adaptive capacities and adaptation strategies of relocated households in rural China - Liu, Wei; Cheng, Yuan; Li, Jie; Feldman, Marcus (Frontiers in Sustainable Food Systems, 2022)
Abstract: Adaptation to environmental change is the focus of sustainability research. Rural households face multiple environmental and social pressures due to global environmental change, so effective livelihood changes must be made to reduce capability losses and adapt to current or future livelihood challenges. Livelihood adaptive capacity and its evaluation provide a new framework for research into the livelihoods of relocated households, we attempt to evaluate the livelihood adaptive capacity of rural households in disaster resettlement areas and to explore how disaster resettlement affects the choice of adaptation strategies. Taking the case of southern Shaanxi as an example, this paper selects indicators from the dimensions of awareness, ability, and action. An index system is constructed for evaluation of farmers' livelihood adaptive capacity, and factors influencing the adaptation strategy are identified by using the multinominal probit regression model. The analysis shows: (1) the most adaptation strategies adopted after disaster resettlement are ‘expansion strategy’, ‘expansion and adjustment strategy’, ‘expansion and assistance strategy’, and ‘expansion and adjustment and assistance strategy’; (2) disaster avoidance relocation has a significant impact on expansion strategies, and whether centralized resettlement has a significant effect on the choice of ‘expansion strategy’ and ‘expansion and adjustment strategy’; and (3) household size, physical assets, and skills training also have a significant impact on the choice of adaptation strategies. Local governments should increase the assistance to the relocated households, improve the households’ livelihood adaptive capacity, and encourage adoption of the most favorable adaptation strategies.